Analisis Determinan Impor di Indonesia Periode 2011 - 2020 - Dwi Kartikasari; Rifki Khoirudin (Ecoplan, 2022)
Imports have the meaning as trade transactions carried out between countries in an effort to meet domestic demand. Imports are not a trade relationship between countries but also an effort to create good relations between countries as an effort to transfer technology from developed countries to countries that are not technologically advanced. Import is one of the efforts made by the state to improve the welfare of its people. Stability between imports and exports is the key in carrying out trade between countries. The main purpose of this study is to determine whether the independent variables used in this study have an effect in the short and long term on imports in Indonesia. The data used in this study is secondary data with a time series period from 2011-2020. The data analysis method used is descriptive quantitative using the Vector Error Correction Model (VECM) analysis tool. The results of this study indicate that in the short term the inflation variable has no significant effect on imports in Indonesia, while the exchange rate variable has a significant effect on imports in the short term. The money supply variable has an effect on imports in the short term and food term, while the interest rate variable has no effect on imports in Indonesia in the short term. In the long terms inflation, the exchange rate and the money supply do not have a significant effect on imports and the interest rate variable has a significant effect on imports in Indonesia.